Jejunoileal atresias - Rosa, Folco (Cirugía del Uruguay, 1973)
Atresia and estenosis of the jejunum and ileum are the most common causes of intestinal occlusion in the newborn. Different types are described. Most significant symptoms are repeated bilious vomiting, followed -or not- by absence of meconioum and flatulence, and by abdominal distention. Radiology comprises plain radiography and contrasted study of the colon. Treatment is always chirurgical. Technics and tactics are considered, as well as the treatment of related malformations. Emphasis is placed on the post-operatory of the massive intestinal resections. Mostality oscillates between 30 and 50 % , being higher when the atrasia is lowest.